Effect of 3-D moderator flow configurations on the reactivity of CANDU nuclear reactors. (January 2017) - Zadeh, Foad Mehdi; Etienne, Stéphane; Chambon, Richard; Marleau, Guy; Teyssedou, Alberto
Highlights: 3-D CFD simulations of CANDU-6 moderator flows are presented. A thermal-hydraulic code using thermal physical fluid properties is used. The numerical approach and convergence is validated against available data. Flow configurations are correlated using Richardson's number. The interaction between moderator temperatures with reactivity is determined. Abstract: The reactivity of nuclear reactors can be affected by thermal conditions prevailing within the moderator. In CANDU reactors, the moderator and the coolant are mechanically separated but not necessarily thermally isolated. Hence, any variation of moderator flow properties may change the reactivity. Until now, nuclear reactor calculations have been performed by assuming uniform moderator flow temperature distribution. However, CFD simulations have predicted large time dependent flow fluctuations taking place inside the calandria, which can bring about local temperature variations that can exceed 50 °C. This paper presents robust CANDU 3-D CFD moderator simulations coupled to neutronic calculations. The proposed methodology makes it possible to study not only different moderator flow configurations but also their effects on the reactor reactivity coefficient.